Cover Image, Volume 53, Issue 6. (23rd June 2020) - Chen, Yaqian; Wang, Yuan; Lin, Weimin; Sheng, Rui; Wu, Yunshu; Xu, Ruoshi; Zhou, Chenchen; Yuan, Quan
Abstract : The cover image is based on the Original Article AFF1 inhibits adipogenic differentiation via targeting TGM2 transcription by Yaqian Chen et al., https://doi.org/10.1111/cpr.12831 .